The Role of Knowledge Management in the Financial Performance of Small and Medium Companies - Zaid, Marwah I; Alqatrani, Russul Isam Noori; Alasadi, Hayder Ali (South Asian Journal of Social Sciences and Humanities, 2023)
This research aims to determine the effect knowledge management processes (knowledge  generation, knowledge distribution, and application knowledge) on financial performance in  the Malaysian small and medium companies. The descriptive analytical secondary and  primary data was utilised as a tool for gathering data from 130 companies as a sample. The  results display that there is a positive association among knowledge management with  financial performance. The knowledge management represented in generation, distribute, and  apply knowledge, and express it about performance through the perspectives of the financial  perspective companies. As the research reached a set of conclusions, including that there the  effect of knowledge management processes on raising level of performance.
Keywords: Knowledge management; financial performance; small and medium companies